Drag and drop the correct steps to solve the equation for x. Make sure to put the steps in order. Not all steps listed will be used.

2(x - 4) - 2x = 2x - 10

8 = 2x - 10
- 8 = 2x - 10
2 = 2x
2x + 8 - 2x = 2x - 10
2x - 8 - 2x = 2x - 10
18 = 2x
x = 9
x = 1

only use the terms given.

5 answers

1. 2(x - 4) - 2x = 2x - 10
2. Distribute the 2 on the left side: 2x - 8 - 2x = 2x - 10
3. Combine like terms on the left side: - 8 = 2x - 10
4. Add 10 to both sides: - 8 + 10 = 2x - 10 + 10
5. Simplify: 2 = 2x
6. Divide both sides by 2: 2/2 = 2x/2
7. Solve for x: 1 = x

The correct order of steps to solve the equation for x is:
1. 2(x - 4) - 2x = 2x - 10
2. Distribute the 2 on the left side: 2x - 8 - 2x = 2x - 10
3. Combine like terms on the left side: - 8 = 2x - 10
4. Add 10 to both sides: - 8 + 10 = 2x - 10 + 10
5. Simplify: 2 = 2x
6. Divide both sides by 2: 2/2 = 2x/2
7. Solve for x: 1 = x
- 8 + 10 = 2x - 10 + 10 isn't a usable option
Apologies for the confusion. Here is the corrected order of steps:

1. 2(x - 4) - 2x = 2x - 10
2. Distribute the 2 on the left side: 2x - 8 - 2x = 2x - 10
3. Combine like terms on the left side: -8 = -10
4. Add 10 to both sides: -8 + 10 = -10 + 10
5. Simplify: 2 = 0
6. Since the equation simplifies to 2 = 0, there is no solution for x.

The correct order of steps to solve the equation for x is:
1. 2(x - 4) - 2x = 2x - 10
2. Distribute the 2 on the left side: 2x - 8 - 2x = 2x - 10
3. Combine like terms on the left side: -8 = -10
4. Add 10 to both sides: -8 + 10 = -10 + 10
5. Simplify: 2 = 0
6. No solution for x
the only options are as followed
8 = 2x - 10
- 8 = 2x - 10
2 = 2x
2x + 8 - 2x = 2x - 10
2x - 8 - 2x = 2x - 10
18 = 2x
x = 9
x = 1
only use four of these to solve the problem
Apologies for the confusion. Here is a revised order of the correct steps to solve the equation for x using only four of the given options:

1. 2(x - 4) - 2x = 2x - 10
2. Distribute the 2 on the left side: 2x - 8 - 2x = 2x - 10
3. Combine like terms on the left side: -8 = -10
4. One of the usable options is -8 = 2x - 10
5. Add 10 to both sides: -8 + 10 = 2x - 10 + 10
6. Simplify: 2 = 2x
7. Divide both sides by 2: 2/2 = 2x/2
8. Solve for x: 1 = x

Using the given options, the correct steps to solve the equation for x are:

1. 2(x - 4) - 2x = 2x - 10
2. Distribute the 2 on the left side: 2x - 8 - 2x = 2x - 10
3. Combine like terms on the left side: -8 = -10
4. One of the usable options is -8 = 2x - 10
5. Add 10 to both sides in step 4: -8 + 10 = 2x - 10 + 10
6. Simplify: 2 = 2x
7. Divide both sides by 2: 2/2 = 2x/2
8. Solve for x: 1 = x